The exorcism of Emily Rose - Linney, Laura; Derrickson, Scott; Wilkinson, Tom, 1948-; Scott, Campbell; Carpenter, Jennifer; Feore, Colm; Stern, Tom; Young, Christopher, 1957-; Sony Pictures Home Entertainment (Firm) ([Culver City, CA] : Sony Pictures Home Entertainment, 2005)
In an extremely rare decision, the Catholic Church officially recognized the demonic possession of a 19 year-old college freshman. Told in terrifying flashbacks, it chronicles the haunting trial of the priest accused of negligence resulting in the death of the young girl believed to be possessed. Middle-aged single lawyer defends Father Moore, a priest on trial for the negligent homicide of a young girl named Emily Rose
Director of photography, Tom Stern ; art director, Sandi Tanaka ; editor, Jeff Betancourt ; music, Christopher Young ; costume designer, Tish Monaghan ; production designer, David Brisbin ; visual effects supervisor, Michael Shelton
Laura Linney, Tom Wilkinson, Campbell Scott, Jennifer Carpenter, Colm Feore, Joshua Close, Ken Walsh, Duncan Fraser
Keywords: Demoniac possession -- Drama; Priests -- United States -- Drama; Lawyers -- United States -- Drama; Feature films; Video recordings for the hearing impaired; Videodiscs